Numerical study on the influence of nozzle spray shape on spray characteristics using diesel and biofuel blends. Issue 9 (21st October 2021) - Ishak, M. H. H.; Ismail, Farzad; Mat, Sharzali Che; Aziz, M. S. Abdul; Abdullah, M. Z.; Abas, Aizat
Abstract: Binary biofuel has a relatively higher viscosity compared to conventional diesel, which affects the spray injection and restricts the maximum evaporation. In this paper, the discrete phase model (DPM) was introduced to study the spray characteristics of four different biofuels, commercial diesel fuel (CDF), pure Melaleuca cajuputi oil, binary blend and ternary blend in a fuel injector. The spray characteristics of various biofuel blends are analyzed and compared to those of pure diesel. A numerical analysis was conducted to study spray characteristics such as Sauter mean diameter (SMD) and penetration for different biofuel blends. Verification and validation from the experimental results and numerical results are also presented. Furthermore, two types of injector hole geometries, cylindrical and conical, are studied. Simulations of the spray evolution are also discussed, highlighting the differences between the use of fossil diesel and biodiesel fuels in terms of spray penetration, atomization and cone angle. Usage of diesel fuel in the conical convergent nozzle gives higher liquid penetration. The results show that the DPM successfully predicted the spray characteristics, such as SMD and penetration of droplet particles, of all biofuel blends.